2015
DOI: 10.1016/j.bbamem.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative EPR studies on lipid bilayer properties in nanodiscs and liposomes

Abstract: Studies of the membrane proteins suggest their close interaction with the lipid surroundings. Membrane proteins and their activities are affected by the composition and structure of the lipid bilayer. therefore adequate surroundings for studied protein are crucial for the model membrane to ensure its biological relevance. In recent years nanodiscs which are small fragments of lipid bilayer stabilised by derivatives of apolipoprotein, called membrane scaffold protein ( MSP), have been established as alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 41 publications
4
51
0
Order By: Relevance
“…Thus, different state of lipids is observed in LPNs in comparison to various bicelles. This is in agreement with the observation that in LPNs lipids are packed tightly and are less mobile than in fluid liposomes 19,20,64 . On the other hand it was shown that LPNs experience phase transitions at temperatures, close to the critical temperatures found for lipid bilayers 63 .…”
Section: Use Of Other Lipids For Bicelle Formationsupporting
confidence: 91%
“…Thus, different state of lipids is observed in LPNs in comparison to various bicelles. This is in agreement with the observation that in LPNs lipids are packed tightly and are less mobile than in fluid liposomes 19,20,64 . On the other hand it was shown that LPNs experience phase transitions at temperatures, close to the critical temperatures found for lipid bilayers 63 .…”
Section: Use Of Other Lipids For Bicelle Formationsupporting
confidence: 91%
“…Various biophysical methods have been used to study lipid-cholesterol interactions, including electron spin resonance (ESR) (Cheng et al, 2014; Delmelle et al, 1980; Hubbell and McConnell, 1971; Lai and Freed, 2014; Manukovsky et al, 2013; Semer and Gelerinter, 1979; Stepien et al, 2015; Vitiello et al, 2015; Williams et al, 2013), Raman (Lippert and Peticolas, 1971; Mendelsohn, 1972; Tantipolphan et al, 2006), Fourier transform infrared (FT-IR) (Umemura et al, 1980), fluorescence spectroscopy (Xu and London, 2000; Yasuda et al, 2015a), atomic force microscopy (AFM), multidimensional NMR spectroscopy (Holland and Alam, 2006; Leftin et al, 2013; Leftin et al, 2014a; Warschawski and Devaux, 2005), solid-state 2 H nuclear magnetic resonance (NMR) (Bartels et al, 2008; Brown, 1990; Bunge et al, 2008; Martinez et al, 2004; Martinez et al, 2002; Matsumori et al, 2012; Stockton et al, 1976; Vogel et al, 2016; Weisz et al, 1992; Yasuda et al, 2015a), and neutron diffraction methods (Armstrong et al, 2014; Toppozini et al, 2014). However, a thorough understanding of the physical basis for these observations in relation to the intricate lipid compositions of many biological membranes to some extent remains an enigma (Feigenson, 2015; McConnell, 2005; Meinhardt et al, 2013; Sodt et al, 2014; Stanich et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…EPR spin probes can be attached to different positions of lipid molecules to report the mobility of the probe and the polarity of its nano-environment. Systematic EPR studies with spin-labeled lipids revealed characteristic fluidity and polarity profiles across liposomal membranes of defined lipid compositions (McConnell and Hubbell, 1971;Marsh, 2001;Subczynski et al, 2010;Stepien et al, 2015). Thus, a biological membrane exhibits not just a single, bulk fluidity and its properties are not sufficiently described by a single number.…”
Section: What Is Membrane Fluidity and How To Measure It?mentioning
confidence: 99%